Self-Perceived Benefits of Cognitive Training in Healthy Older Adults - Goghari, Vina M.; Lawlor-Savage, Linette (Frontiers in Aging Neuroscience, 2018)
The idea that individualized, computer-based cognitive training improves cognitive functioning in non-trained domains is highly contested. An understudied area is whether cognitive training improves one’s own perception of cognitive and day-to-day functioning. Furthermore, no studies have compared working memory training to programs that train higher-level processes themselves, namely logic and planning, in improving perception of cognitive abilities. We investigated self-reported changes in a) cognitive errors relevant to daily life, b) expectations regarding training, and c) impact of training on daily life, in healthy older adults who completed working memory training or logic and planning training. Ninety-seven healthy older adults completed 8-weeks of computerized cognitive training that targeted either working memory or logic and planning. Findings were compared to a no-training control group. Participants reported fewer cognitive failures relevant to daily life after training compared to the no-training control group, with a greater reduction in errors reported by the logic and planning training group compared to the working memory training group. Trainees’ perception of training efficacy decreased over time. Nonetheless, approximately half of the participants in both training groups endorsed “some improvement” or more in self-perceived day-to-day functioning at post-testing. These results support the conclusion that individualized computerized cognitive training may enhance subjective perceptions of change and that higher level cognitive training may confer additional benefits. Findings suggest that cognitive training can enhance cognitive self-efficacy in healthy seniors.